2017
DOI: 10.1080/09674845.2017.1392736
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the comparability of CLSI, EUCAST and Stokes antimicrobial susceptibility profiles for Escherichia coli uropathogenic isolates

Abstract: Our data indicate that the discrepancies generated through using different AST methods and different interpretive guidelines may result in confusion and inaccuracy when prescribing treatment for urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Zone diameter data for first-line antimicrobial agents tested according to CLSI standards against all non-duplicate (first isolate per patient) clinical isolates of Escherichia coli , Klebsiella pneumoniae , and Pseudomonas aeruginosa from 1 January 2017 to 31 December 2017 were extracted from the Laboratory Information Management System and interpreted separately using EUCAST 2018 [2] and CLSI 2018 [3] breakpoints as susceptible, intermediate, or resistant and category agreement (percentage of isolates with the same result) determined. These organisms were selected as they were the commonest Gram-negative isolates in 2017 for which both organisations provide clinical breakpoints, and recent studies have reported discrepancies in their susceptibility interpretation [4] , [5] .…”
mentioning
confidence: 99%
“…Zone diameter data for first-line antimicrobial agents tested according to CLSI standards against all non-duplicate (first isolate per patient) clinical isolates of Escherichia coli , Klebsiella pneumoniae , and Pseudomonas aeruginosa from 1 January 2017 to 31 December 2017 were extracted from the Laboratory Information Management System and interpreted separately using EUCAST 2018 [2] and CLSI 2018 [3] breakpoints as susceptible, intermediate, or resistant and category agreement (percentage of isolates with the same result) determined. These organisms were selected as they were the commonest Gram-negative isolates in 2017 for which both organisations provide clinical breakpoints, and recent studies have reported discrepancies in their susceptibility interpretation [4] , [5] .…”
mentioning
confidence: 99%
“…During our studies, association between applied interpretation criteria and susceptibility patterns, as well as different phenotypes of resistance to selected antimicrobials among opportunistic haemophili rods were detected. Many authors 14 20 point to the differences occurring at the following fields: categorization of drug susceptibility, assignment to individual beta-lactam phenotypes of resistance in Haemophilus spp. bacteria, as well as CLSI 21 and EUCAST 22 cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, values for both evaluation criteria are constantly evolving when new data become available and those with the greatest differences (eg ciprofloxacin in E. coli) tended to converge over time. 94 The main task of surveillance systems is to provide an overview of patterns and trends, however some systems may provide additional useful information for risk factor analysis.…”
Section: Amr Surveillance and Monitoring Systemsmentioning
confidence: 99%